1916. Evaluation of nasal swab collection methods on a university campus during the SARS-CoV-2 pandemic. (15th December 2022) - O'Hanlon, Jessica A; Acker, Zack; Bennett, Julia C; Han, Peter D; McDonald, Devon; Wright, Tessa; Luiten, Kyle G; Regelbrugge, Lani; McCaffrey, Kathryn; Pfau, Brian A; Wolf, Caitlin R; Pothan, Lincoln C; et al.
Abstract: Background: Characterizing SARS-CoV-2 outbreaks on university campuses is critical for informed public health measures and understanding transmission dynamics. Figure 1. Dropbox and Kiosk Samples Collected September 10, 2021 to April 23, 2022. Methods: Faculty, staff, and students at a major public university in Seattle, WA, USA were enrolled in a COVID-19 testing study. Individuals could test using observed self-swabs at on-campus kiosks or unobserved self-swabs using a kit and returning it to a dropbox on campus. Sample collection volume for observed self-swabs was limited by staffing and space. All samples were returned to the laboratory and tested for SARS-CoV-2 by qRT-PCR. Results: From September 10, 2021 to April 23, 2022, 38, 400 individuals were enrolled in the study. Of these individuals, 5, 089 used dropboxes only, 14, 421 used kiosks only, and 5, 820 used both. A total of 21, 653 dropbox swabs and 75, 493 observed self-swabs were collected. Median age was similar between individuals using dropboxes and observed self-swabs (20 vs. 22 years). A greater proportion of dropbox users were students compared to faculty and staff (students made up 83% of dropbox only population, 75% of kiosk only, and 86% of both, χ² p-value< 0.0001). Symptom data was reported for 65, 349 swabs. Dropbox users were less likely to have symptoms compared to observed self-swab users (24% of swabs vs. 54%, χ² p-value< 0.0001). SARS-CoV-2 positivity was slightly lower for dropboxes compared to kiosks (4% vs. 5%; p=0.001). Dropboxes were highly utilized during periods of increased testing demand, including after academic breaks and variant emergence (Figure 1). Of the total tests distributed for use, a greater proportion of dropbox kits were unable to be resulted (6%) compared to observed self-swab kits (0.02%). Conclusion: Dropboxes provided a flexible, high-volume collection method at times of increased testing demand. Individuals who used dropboxes were less likely to report symptoms and slightly less likely to test positive, suggesting a role for dropbox utilization in high-risk asymptomatic individuals during periods of high community transmission on a university campus. Disclosures: Geoffrey S. Gottlieb, MD, PhD, Abbott Molecular Diagnostics: Grant/Research Support|Alere Technologies: Grant/Research Support|BMGF: Grant/Research Support|BMS: Grant/Research Support|Cerus Corp.: Grant/Research Support|Gilead Sciences: Grant/Research Support|Janssen Pharmaceutica: Grant/Research Support|Merck & Co: Grant/Research Support|Roche Molecular Systems: Grant/Research Support|THERA Technologies/TaiMed Biologics: Grant/Research Support|ViiV Healthcare: Grant/Research Support Helen Y. Chu, MD, MPH, Cepheid: Reagents|Ellume: Advisor/Consultant|Gates Ventures: Grant/Research Support|Merck: Advisor/Consultant|Pfizer: Advisor/Consultant.